Across borders: thoughts and considerations about cultural preservation among immigrant clinicians. (11th January 2019) - Ashing, Kimlin Tam; Dawkins-Moultin, Lenna; George, Marshalee; Antoine, Gerard M; Nunez-Smith, Marcella; Pérez-Stable, Eliseo J
Abstract: Immigrant clinicians make up 20–28% of the health workforce in many high-income countries, including Australia, Britain, Canada and the USA. Yet, the preserved culture of immigrant clinicians remains largely invisible in the medical literature and discourse. Research on immigrant clinicians primarily attends to medical professional requirements for the adopted country (medical board examination eligibility, fellowship training and licensing). Cultural preservation among immigrant clinicians has not been adequately considered or studied. This paper highlights this notable gap in healthcare delivery and health services research relevant to immigrant clinicians. We propose it is worthwhile to explore possible relationships between immigrant clinicians' preserved culture and clinical practices and outcomes since immigrant clinicians cross borders with their academic training as well as their culture. The sparse literature regarding immigrant clinicians suggests culture influences health beliefs, attitudes about the meaning of illness and clinical practice decisions. Additionally, immigrant clinicians are more likely to serve rural, low-income populations; communities with high density of ethnic minorities and immigrants; and areas with primary care shortage. Therefore, cultural preservation among immigrant clinicians may have important implications for public health and health disparities. This area of inquiry is important, if not urgent, in health services research.